FORMULATION AND EVALUATION OF ORODISPERSIBLE TABLETS OF DONEPEZIL HYDROCHLORIDE - KUMARI, P. V. KAMALA; RAO, Y. SRINIVASA (International Journal of Current Pharmaceutical Research, 2020)
Objective: The present study was aimed to develop the formulation and in vitro evaluation of Orodispersible tablets by wet granulation method using Donepezil HCl as a model drug to enhance patient compliance. Methods: In the wet granulation method, a mixture of microcrystalline cellulose and hydroxypropyl methylcellulose were used along with superdisintegrants, i.e., croscarmellose sodium and crospovidone. The prepared granules were subjected to both pre and post-compression evaluation parameters including; FTIR spectroscopy, micromeritics properties, tablet weight variation, hardness, friability, drug content, disintegration time and in vitro drug release. Results: FTIR studies indicated that there was nointeraction between the drug and the excipients used. The formulation containing high concentration of crospovidone and mixture as the best formulation F2 based on in vitro drug release characteristics of tablet formulation. Conclusion: The results of this work suggested that orodispersible tablets of Donepezil hydrochloride with rapid disintegration time, fast drug release and good hardness can be efficiently and successfully formulated by wet granulation method.